Walt Whitman, philosopher poet "Leaves of grass" by indirection - McDonald, John W. (McFarland, 2007)
"This volume contains an extensive study of Walt Whitman's poetry that explores both Whitman's guiding philosophy and its uses to unlock meaning within Leaves of Grass. Beginning with a detailed explanation of determinism, the author examines Whitman's use of indirection, which the poet referred to at times as a game played to evade the reader's comprehension."--Provided by publisher.
Includes bibliographical references and index
Keywords: Whitman, Walt -- 1819-1892 -- Leaves of grass; Whitman, Walt -- 1819-1892 -- Philosophy; Whitman, Walt <1819-1892> -- Leaves of grass; Philosophie; Philosophy in literature; Determinism (Philosophy); Determinismus -- Motiv